(untitled) (Scientific journal of the Fergana State University, 2024)
The article is devoted to the study of the chemical components of the aerial part of the plant Lophanthus schtschurowskianus (Regel) Lipsky of the Lamiaceae family. From various fractions of 80% ethanol extract of plant materials, succinic acid, cynaroside (luteolin-7-O-β-D-glucopyranoside) and luteolin-7-O-rutinoside were isolated and identified based on the study of spectral data and chemical transformations.